Correlation Between the Z-Transform and Laplace Transform in Discrete-Time Signals - Malla, Mohan Bikram; Baral, Aasis (Mid-West University Journal of Engineering & Innovation, 2025)
This paper focuses on introducing Z-transform and Laplace transform, as well as exploring the relationship between them. The z-transform’s function in the analysis of discrete-time single and LTI systems is reviewed, as is the role of the Laplace transform in the study of continuous-time signals and L.T.I., as well as what the particular region of convergence represents. The area of convergence has been illustrated graphically, and the relationship is examined. This paper starts by deriving the z-transform from the Laplace transform applied to a discrete-time signal.